Proteomics alterations in chicken jejunum caused by 24 h fasting - Ádám Simon; Gabriella Gulyás; Zoltán Mészár; Mangesh Bhide; János Oláh; Péter Bai; Éva Csősz; András Jávor; István Komlósi; Judit Remenyik; Levente Czeglédi (PeerJ, 2019)
The small intestine is the longest part of the chicken (Gallus gallus) gastrointestinal system that is specialized for nutrient absorption. It is known that decrease in intestinal villi area or height in early age can cause a reduction in essential nutrient intake, which may lead to delayed growth and consequently poorer performance of broiler chickens. The small intestinal absorptive surface is known to be affected by various factors, among others things the nutritional state. In our experiment, we aimed to investigate the possible protein expression alterations that lie behind the villus area and height decrease caused by feed deprivation. A total of 24 chickens were divided into three groups, namely ad libitum fed, fasted for 24 h, fasted for 24 h then refed for 2 h. The morphometric parameters were also measured in the duodenum, jejunum and ileum tissue sections using image analysis. Differential proteome analyses from jejunum samples were performed using two-dimensional difference gel electrophoresis followed by tryptic digestion and protein identification by matrix-assisted laser desorption/ionization mass spectrometry. Overall 541 protein spots were detected after 2D. Among them, eleven showed 1.5-fold or higher significant difference in expression and were successfully identified. In response to 24 h fasting, the expression of nine proteins was higher and that of two proteins was lower compared to the ad libitum fed group. The functions of the differentially expressed proteins indicate that the 24 h fasting mainly affects the expression of structural proteins, and proteins involved in lipid transport, general stress response, and intestinal defense.